Preparation and Application Progress of Polyethylene Hollow Fiber Ion-Exchange Membrane - Li, Changyou; Zhang, Yanhua (Asian Journal of Chemistry, 2012)
In the paper, preparations of polyethylene hollow fiber ion-exchange membranes are described. Generally, the preparations consist of three steps: First, free radicals are produced on the surface of polyethylene hollow fiber membranes using g-ray or electron beam. Second, pre-functional groups are introduced when monomer reacts with free radicals. Finally, polyethylene hollow fiber ion-exchange membranes are produced when reagents react with pre-functional groups. In addition, applications of membranes in the protein separation, metal ion removal and enzyme immobilization are also described, which is helpful to research on preparations of hollow fiber ion-exchange membranes for other materials.